THE HISTOPATHOLOGY OF PSORIASIS - C. Mignogna; G. De Rosa (PAGEPress Publications, 2011)
Psoriasis is a common, chronic, relapsing, papulo-squamous dermatitis, with overlying silvery scales. The scalp, sacral region, and extensor surfaces of extremity are commonly involved, even if flexural and intertriginous areas may be affected in the so-called "inverse psoriasis". Involvement of nails is frequent. Oral lesions (geographic stomatitis and/or glossitis) are commonly described. 5-8% of psoriatic patients develop arthritis. Interphalangeal joints are characteristically involved, but large joints are also affected. From a histological point of view, psoriasis is a dynamic dermatosis that changes during the evolution of an individual lesion; we can classify it in an early stage, advanced stage, and later lesions. Lesions are usually diagnostic only in early stages or near the margin of advancing plaques. Munro microabscesses and Kogoj micropustoles are diagnostic clues of psoriasis, but they aren't always present. All other features can be found in numerous eczematous dermatitis. Key words: Psoriasis, histopathology, immunohistochemistry